STARVING BLACK: A STUDY ON MAYA ANGELOU’S SELECT POEMS (International Journal of Food and Nutritional Sciences, 2022)
Among the African American writers, Maya Angelou has grabbed the attention of masses all over the world. Her poems provide an in depth understanding of the Africans who live in America. Named African American or a Negro or a Nigger, these people face a variety of injustices in America. Hunger is one of the pains inflicted on the African Americans. Angelou expresses the situation of starving Blacks and the rich Whites in the selected poems. The Blacks are very hard working, but usually they are denied the basic necessities of life. The poor people are put in such a situation where the mothers stoop too much for bringing up their own children. But Angelou tells the readers that this situation can be changed if all people work unanimously.